DETERMINAN KEPUTUSAN BERKUNJUNG KE RESTORAN HOTEL BERSERTIFIKASI HALAL DI KOTA MATARAM NTB - Rosida Rusmiati (Fakultas Syariah IAI Hamzanwadi Pancor, Lombok Timur, Indonesia, 2022)
Indonesia has a great potency in the development of Halal Tourism Destination, Moslem Friendly Tourism Destination and Sharia Tourism. The existence of these terms is the answer for the negative view and the unproductiveness of tourism sector particularly for the national or international Moslem travelers. In fact, such tourism is a part of the need of human life. The potency of the halal tourism industry must be supported by developing more halal certified hotel restaurants that in this case becomes the preference not only for the Moslems but also for the non-Moslems in consideration to that the halal food must be healthy. Many products that have no halal certificate has led the customers, particularly the Moslem customers find it difficult to differentiate which products that are really halal and can be consumed in accordance with the Islam law. This research aims to observe the determining factor and the most dominant factors in the decision of customers to visit the halal certified hotel restaurants in Mataram City, NTB. The research method was conducted qualitatively with the doubled regression model and analysis of Ordinary Lease Square (OLs). The result of this research showed that the independent variables (religion, personality, and psychology) had a significantly positive impact on the dependent variables (decision of customers to visit the hotel restaurant in Mataram City, NTB). The dominant factor determining the customers to visit the halal certified hotel restaurant included the personal, religious and psychological factors. Meanwhile, the most dominant factor was the personal factor with the level of the significantly positive impact (t count of 5.911, Sig t:0.00) on the dependent variables obtaining the value of R² 0.9 meaning that 49.4% independent variable in this research was impacted by the factors in this research. On the other hand, the rest of it (50.4%) was influenced by other factors outside this research.